2012
DOI: 10.1093/infdis/jis591
|View full text |Cite
|
Sign up to set email alerts
|

Influenza and Malaria Coinfection Among Young Children in Western Kenya, 2009–2011

Abstract: Coinfection with malaria and influenza was uncommon but associated with longer hospitalization than single infections among children 24-59 months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…A retrospective, cross-sectional study in western rural Kenya has addressed this issue. The study found that 45% (149/331) of influenza-positive patients were coinfected with malaria, whereas only 6% (149/2408) of malaria-positive patients were coinfected with influenza [36]. Coinfection with malaria and influenza was uncommon but associated with longer hospitalization than single infections among children 24-59 months of age [36].…”
Section: Co-morbidity: Influenza-hiv Influenza-chronic Lung Diseasementioning
confidence: 91%
“…A retrospective, cross-sectional study in western rural Kenya has addressed this issue. The study found that 45% (149/331) of influenza-positive patients were coinfected with malaria, whereas only 6% (149/2408) of malaria-positive patients were coinfected with influenza [36]. Coinfection with malaria and influenza was uncommon but associated with longer hospitalization than single infections among children 24-59 months of age [36].…”
Section: Co-morbidity: Influenza-hiv Influenza-chronic Lung Diseasementioning
confidence: 91%
“…Co-infection with malaria and influenza in young African children is associated with longer hospitalization than single infections in the same population, 73 while more complications are seen in co-infections with P. vivax and dengue virus in French Guyana than in single-pathogen infections. 74 However, most studies suggesting an adverse effect of viral infection on malaria-related outcomes refer to co-infections with P. falciparum and HIV in sub-Saharan Africa.…”
Section: Co-infections With Virusesmentioning
confidence: 99%
“…None of the studies investigated the aetiologies of fever in children under 5 years in sub-Saharan Africa by screening all relevant foci of infection, thus BSI, UTI, RTI and GII together. Patients included in the studies who were selected for our review were outpatients [23][24][25][26], inpatients [20,[27][28][29][30][31][32][33] or the both [18,[34][35][36][37][38]. The mortality rate in the studies that provided this specific information ranged from 1.4 to 22.5% and specifically concerned the inpatient studies [18,20,28,29,33,34].…”
Section: Aetiologies Of Fever In Children Under 5 Yearsmentioning
confidence: 99%
“…Bacteria isolated from UTI were predominately E. coli (six of six) and Klebsiella ssp (six of six), with positive rates of 20.0-72.3% and 10.0-28.5%, followed by Staphylococcus, Proteus and Pseudomonas ( Table 2). Samples were analysed in district hospitals [18,27,28,30,[35][36][37], reference hospitals [32,38], teaching hospitals [20,23,29,35] or reference laboratories [24,26,34].…”
Section: Aetiologies Of Fever In Children Under 5 Yearsmentioning
confidence: 99%